Efeitos da aplicação do foam rolling na recuperação de propriedades musculotendíneas e parâmetros funcionais de flexores plantares de indivíduos saudáveis - Rodrigues, Deivid Ribeiro (2022)
The aim of this study was to verify the effects of foam rolling (FR) application on the recovery of mechanical and functional properties of plantar flexors muscles in healthy individuals. Twenty-eight men (18-40 years) participated, who were divided into two groups: foam rolling or control. The stiffness of the aponeuroses (superficial and deep) and muscle of the triceps surae was evaluated using shear wave elastography. Delayed onset muscle soreness (DOMS) was obtained by applying the visual analogue pain scale. Range of motion (ROM) and peak torque were evaluated using an isokinetic dynamometer, and vertical jump height using a kinematics system. The evaluations took place before, immediately after, and 24h, 48h and 72h after performing an exercise-induced muscle damage (EIMD) protocol (4x25 maximal eccentric contractions). EIMD promoted an increase in stiffness of the superficial aponeurosis immediately after, while muscle stiffness remained high for up to 72 hours. However, DMIE did not promote changes in the deep aponeurosis stiffness. DOMS increased from 24h, ROM was not changed, and jump height and force production decreased up to 24h and 48h, respectively. The application of FR after EIMD resulted in a reduction in DOMS compared to the control group within 72 hours. In the other parameters, the groups were similar. The application of FR may be a strategy to reduce DOMS (probably by neural factors), but it does not seem to influence the recovery of myofascial tissue stiffness and other functional properties of the plantar flexors.